JASAD RENIK DALAM FERMENTASI MINUMAN KHAMR: PERSPEKTIF AL-QUR’AN DAN SAINS - Yaya Ruhayyah; Erni Koyimah (Al Kareem Jurnal Ilmu Al Qur'an dan Tafsir, 2024)
This research aims to examine the presence of microorganisms in the fermentation process of khamr drinks from the perspective of the Al-Qur’an and Science. In Science, fermentation is a biochemical process that involves microorganisms such as Saccharomyces cerevisiae in converting sugar into alcohol and carbon dioxide. This process is the basis for making various alcoholic drinks. On the other hand, the Al-Qur’an strictly prohibits the consumption of khamr because of its negative impact on human reason and morals. This research uses a qualitative method by reviewing literature (library research), namely collecting writings or books, journals, and commentaries as well as scientific analyzes regarding fermentation. The research results show that although science explains the important role of microorganisms in fermentation, the Koran directs humanity to stay away from khamr in order to maintain physical, mental and spiritual health. This study provides an integrative understanding of the relationship between religious teachings and scientific findings related to khamr, as well as their relevance in modern life.